Traffic engineering handbook - Pande, Anurag; Wolshon, P. Brian (John Wiley & Sons Inc., 2015)
"The Traffic Engineering Handbook is a comprehensive practice-oriented reference that presents the fundamental concepts of traffic engineering, commensurate with the state of the practice"--